Exploring the Nexus Between Calculator Competency and Higher-Order Thinking Skills in Quadratic Functions: A Needs Analysis for Malaysian Secondary Mathematics Education - Zi Jun Leong; Norulhuda Ismail (Journal of the Indonesian Mathematics Education Society, 2026)
The study investigates how scientific calculator proficiency affects Malaysian Form 4 students' Higher-Order Thinking Skills (HOTS) advancements when studying quadratic functions. The research study has become relevant because international and national educational systems now consider HOTS development as a fundamental requirement for their mathematics programs. The researchers used a quantitative correlational needs analysis framework to study 98 students who attended national secondary schools in Johor, whom they selected through stratified random sampling. The assessment process used two tools, which included a Calculator Competency Assessment (CCA) and a HOTS Proficiency Test (HPT). The students achieved calculator skills at a high level (M = 8.28/10, SD = 1.56), but their performance on HOTS assessments remained at a much lower level (M = 10.74/25, SD = 8.26). The study found a moderate positive relationship between calculator skills and HOTS performance, which showed an effect size of 0.547 and a p-value below 0.001. Calculator competency showed weak connections to two analytical tasks which needed analysis skills, according to item-level analysis results. The results show that educators who currently teach students do not use calculators as effective teaching resources which help students develop their advanced thinking skills. The results demonstrate that educational materials should connect calculator implementation with activities that require higher-order thinking skills instead of treating calculator operation as separate skills.